Pengaruh Kompetensi Pramusaji Terhadap Kualitas Pelayanan Restoran di Kota Tomohon - Miriam Mahdalena Tukunang (PolimdoSains, 2020)
This study aims to analyze how the competency of waitresses influence the service quality of restaurant in the city of Tomohon today. There are several elements that become the standard to become professional waiters, namely, Skill, Knowledge and Attitude and three elements that are measured in determining the level of service quality, namely Reliability, Responsiveness and Assurance. Understanding competency steward is the ability of individuals in their work or a basic character depicted on an effectiveness or good performance in a particular place and situation. The analysis used in this research is quantitative analysis with a simple correlation data analysis method to determine the level of competence of waiters for service quality. The analysis of the coefficient of determination to find out how much the competence of the waitresses affect the quality of service. The analysis results obtained the correlation value where r = 1.735 which states that the strong influence between the competency of the waiter on the quality of restaurant service in Tomohon City then the coefficient of determination is KD = 54.1% on the quality of service. From these results it can be said that the influence of the waiter competence variable by 54.1% on service quality and the remaining 45.9% is influenced by other factors.The results showed that the competency of waitresses was very influential on the quality of restaurant services in the of Tomohon. Therefore, the supervisors in each restaurant need to be able to provide training or provide opportunities for employees to develop themselves by attending trainings conducted by the government or in collaboration with other competent parties such as the Professional Certification Board which receives direct supervision from the National Professional Certification Agency.